Magnetic X-ray spectroscopy studies of dilute magnetic semiconductors - Freeman, Adam Alexander (2009)
Dilute magnetic semiconductors are an important family of materials that have many potential applications in spintronics; (Ga,Mn)As, (In,Ga,Mn)As and (Ga,Mn)N are of major interest. This thesis investigates dierent aspects of these, using the synchrotron radiation techniques of x-ray magnetic circular dichroism (XMCD) and x-ray magnetic linear dichroism (XMLD), supported by superconducting quantum interference device (SQUID) magnetometry and magnetotransport measurements.